Delineation of the HPV11E6 and HPV18E6 Pathways in Initiating Cellular Transformation - Mwapagha, Lamech M.; Tiffin, Nicki; Parker, M. Iqbal (Frontiers in Oncology, 2017)
Although high-risk human papillomaviruses (HPVs) are the major risk factors for cervical cancer they have been associated with several other cancers such as head and neck and oral cancers. Since integration of low-risk HPV11 DNA has been demonstrated in oesophageal tumour genomes, this study compared the effects of low-risk HPV11E6 and high-risk HPV18E6 on cellular gene expression. The HPV11E6 and HPV18E6 genes were cloned into an adenoviral vector and expressed in human keratinocytes (HaCaT) in order to investigate early events and to eliminate possible artefacts introduced by selective survival of fast growing cells in stable transfection experiments. HPV11E6 had very little effect on p21 and p53 gene expression, while HPV18E6 resulted in a marked reduction in both these proteins. Both HPV11E6 and HPV18E6 enabled growth of colonies in soft agar, but the level of colony formation was higher in HPV18E6 infected cells. DNA microarray analysis identified significantly differentially regulated genes involved in the cellular transformation signalling pathways. These findings suggest that HPV11E6 and HPV18E6 are important in initiating cellular transformation via deregulation of signalling pathways such as PI3K/AKT and pathways that are directly involved in DNA damage repair, cell survival and cell proliferation. This study shows that the low-risk HPV11E6 may have similar effects as the high-risk HPV18E6 during the initial stages of infection, but at a much reduced level